Activated Carbons as Effective Adsorbents of Non-Steroidal Anti-Inflammatory Drugs - Małgorzata Wasilewska; Elżbieta Grządka (Applied Sciences, 2024)
In this study, the adsorption of naproxen sodium, ibuprofen sodium, and diclofenac sodium on activated carbon is investigated. Comprehensive studies of adsorption equilibrium and kinetics were performed using UV-Vis spectrophotometry. Thermal analysis and zeta potential measurements were also performed for pure activated carbon and hybrid materials (activated carbon–drug) obtained after adsorption of naproxen sodium, ibuprofen sodium, and diclofenac sodium. The largest amount and rate of adsorption was demonstrated for naproxen sodium. A significant impact of temperature on the adsorption of the tested salts of non-steroidal anti-inflammatory drugs was also indicated. Faster kinetics and larger amounts of adsorption were recorded at higher temperatures. Thermodynamic parameters were also determined, based on which it was indicated that adsorption in the tested experimental systems is an endothermic, spontaneous, and thermodynamically privileged process of a physical nature. The generalized Langmuir isotherm was used to study the equilibrium data. The adsorption rate data were analyzed using numerous adsorption kinetics equations, including FOE, SOE, MOE, f-FOE-, f-SOE, f-MOE, and m-exp.